Cork oak and climate change: disentangling drought effects on cork chemical composition - Leite, Carla (2020)
Climate change induces in the Mediterranean region more frequent and extreme events, namely, heat waves and droughts, disturbing forest species and affecting their productivity and product quality. The cork oak (Quercus suber) is present along the western Mediterranean basin and its outer bark (cork) is sustainably collected and used for several products, mainly wine bottle stoppers. Since most cork properties arise from its chemical composition, this research studies the effect of drought on cork chemical composition (suberin, lignin, polysaccharides and extractives) and on polysaccharide and suberin monomeric composition. Three sets of cork samples, from the same site, were examined: in one set the cork grew without drought; in another two drought events occurred during cork growth and in the third one drought event happened. The results show that, in general, drought does not affect the proportion of the main components of cork, the monomers of suberin or of polysaccharides, with few exceptions e.g. drought increased ethanol extractives and xylose in polysaccharides and decreased arabinose in polysaccharides. The variability associated to the tree is much more relevant than the effect of drought conditions and affects all the parameters analyzed. Therefore, our research suggests that the tree genetic information, or its expression, plays a much more important role on the chemical composition of cork than the drought conditions occurring during cork growth. In practical terms, the potential increased occurrence of droughts arising from climatic changes will not compromise the performance of cork as a sealant for wine bottles